Early Childhood Stimulation in Toddler Twins : a Case Study - Darmawati, Irma; Nurlela, Ratu (Indonesian Journal of Community Development, 2024)
Background : The critical period for children occurs between the ages of 6-24 months. This age group is a period of crucial growth and potential failure to thrive, especially in twins. Stimulation activities such as singing, storytelling, and playing can optimize children's development. Objective: This study aims to describe nursing care by providing early childhood stimulation to twins. Methods: This research was conducted using a case study approach, observing changes in children's behavior during early childhood stimulation interventions. Results: After providing developmental stimuli such as singing, playing, and storytelling for 3 days, it was found that the child's development had changed. Children who initially did not respond now responded, those who were initially passive were now able to follow commands, and there was improvement in the pronunciation of words. Conclusion: This study provides evidence to support the importance of stimulating children's development from an early age. Community nurses are advised to educate mothers in their work area on how to stimulate growth and development to prevent developmental delays or failure to thrive in twins.